Decomposition of the Sources of Real Exchange Rate Misalignment in Egypt: Evidence from the ARDL Model: An Evidence from ARDL Model - Hosni, Rana (Organizations and Markets in Emerging Economies, 2021)
This paper examines the behavior of the real exchange rate in Egypt over the period 1965–2018 by attempting to pursue three interrelated purposes. The first is to investigate the extent of deviations between the actual exchange rate and its equilibrium level and illustrate the magnitude of any currency misalignments. The second is to search for the different phases of over- and undervaluation of the local currency and explain the accompanying economic policies and/or factors leading to them. The third and ultimate purpose is to explore the role of transitory and permanent factors in deviating the actual real exchange rate from its equilibrium level. Understanding these factors should help in the design of economic policies directed to address the misalignment of the local currency. An autoregressive distributed lag (ARDL) bound test approach is used and conducted for both the bilateral and effective real exchange rates to achieve these three purposes during the selected period. To derive the equilibrium exchange rate estimate, the behavioral equilibrium exchange rate (BEER) approach is adopted. The findings reveal that the Egyptian pound was misaligned from its equilibrium value during most of the examined period. The results confirm the relative importance of the terms of trade and degree of openness variables in determining the equilibrium real exchange rate in Egypt followed by investment ratio and government consumption variables. The local currency witnessed a recent phase of overvaluation, which began in 2009, until the free float of the local currency in November 2016, after which, the Egyptian pound was found to have experienced a new phase of undervaluation till the end of the period examined. The findings show a considerable relative impact of fundamental-based factors over a prolonged period spanning from 1986 to 2003 and at the end of the period examined as well. Moreover, the documented results lend general support to the fact that both permanent or fundamental-based factors and short-run shocks prove to be important influential factors impacting currency misalignment in Egypt.